2017
DOI: 10.1177/0886260517726972
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing Sexual Violence in Intimate Relationships: An Examination of Blame Attributions and Rape Acknowledgment

Abstract: Rape by an intimate partner frequently involves a precedence of sexual consent between victim and perpetrator, often does not include the use of physical force, and may not fit societal definitions of rape. Given these unique characteristics, women who are assaulted by an intimate partner may be less likely to acknowledge the experience as a rape. In turn, they might make fewer blame attributions toward themselves and their perpetrators than victims of rape by a nonpartner. Consistent with these expectations, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
28
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 55 publications
4
28
0
1
Order By: Relevance
“…They may also be reluctant to identify with some forms of abuse. For example, in the context of a relationship where there has been prior consensual sex, a woman may be more hesitant to label an event as coerced or forced sex, even if consent was not given 56 . However, even physical violence, the most tangible form of violence, is difficult to measure in different contexts and tools vary in their comprehensiveness, affecting calculated prevalence rates 53 …”
Section: Minimizing and Responding To Risks Of Harm In Srh Digital Inmentioning
confidence: 99%
“…They may also be reluctant to identify with some forms of abuse. For example, in the context of a relationship where there has been prior consensual sex, a woman may be more hesitant to label an event as coerced or forced sex, even if consent was not given 56 . However, even physical violence, the most tangible form of violence, is difficult to measure in different contexts and tools vary in their comprehensiveness, affecting calculated prevalence rates 53 …”
Section: Minimizing and Responding To Risks Of Harm In Srh Digital Inmentioning
confidence: 99%
“…It has been found that 8.8% of women in the United States of America have been raped by their partners (Breiding, 2015), indicating that IPSV is a serious problem across different cultural contexts. Given that sexual violence can exist alongside physical and psychological violence, the health repercussions can become highly dangerous (Alsaker et al, 2011;Jaffe et al, 2017). However, though the prevalence and consequences of physical violence by partners have been widely documented, little is known about IPSV (Pengpid et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Participants could choose one response from the following: intimate partner, friend, acquaintance, and stranger. Follow-up questions after the SES-SFV have been commonly used for identifying IPSV and other assault characteristics (Littleton & Henderson, 2009;Jaffe, Steel, DiLillo, Messman-Moore, & Gratz, 2017).…”
Section: Methodsmentioning
confidence: 99%